2020
DOI: 10.1002/jsfa.10689
|View full text |Cite
|
Sign up to set email alerts
|

Physico‐chemical characterization of Cornus kousa Burg. fruit: determining optimal maturity for fresh consumption

Abstract: BACKGROUND: Japanese dogwood (Cornus kousa Burg.) is a popular ornamental plant which develops edible compound fruit utilized in traditional Asian medicine. Previous compositional studies have focused on a small fraction of secondary metabolites at a single maturity stage. In order to address the question of optimal ripeness of Japanese dogwood fruit for consumption the study provides a comprehensive insight into its primary and secondary metabolic profile. RESULTS: The aim of the study was to investigate bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…In this species, high amounts of cyanidin 3-O-glucoside are found, followed by cyanidin 3-O-galactoside and very small quantities of delphinidin 3-O-glucoside [11]. A recent study reported pelargonidin 3-O-galactoside in C. kousa fruits ( [57]).…”
Section: Flavonoids and Proanthocyanidinsmentioning
confidence: 84%
See 4 more Smart Citations
“…In this species, high amounts of cyanidin 3-O-glucoside are found, followed by cyanidin 3-O-galactoside and very small quantities of delphinidin 3-O-glucoside [11]. A recent study reported pelargonidin 3-O-galactoside in C. kousa fruits ( [57]).…”
Section: Flavonoids and Proanthocyanidinsmentioning
confidence: 84%
“…Similar to other Cornus species, fruits of C. kousa are characterised by quercetin derivatives (quercetin 3-O-galactoside, quercetin 3-O-xyloside and quercetin 3-O-glucoside) and by kaempferol and myricetin heterosides [57,61,62]. The principal flavonoids and proanthocyanidins found in Cornus fruits are reported in Table 2.…”
Section: Flavonoids and Proanthocyanidinsmentioning
confidence: 85%
See 3 more Smart Citations